Utilization of Multi-Media Games as a Pedagogical Approach - Lauro C Malvecino; Randy Joy M Ventayen (ASEAN Multidisciplinary Research Journal, 2020)
Quality education is anchored on the effectiveness of pedagogical skills of the teachers who are at the forefront of the thrust of the Department of Education. This study aimed to determine the effectiveness of multimedia games as a pedagogical tool in improving the cognitive and affective skills of the learners. Descriptive method of research was employed with the questionnaire as the main data-gathering instrument.  Data gathered were subjected to descriptive and inferential treatment. Moreover, this study made use of the frequency counts and percentages for the profiling of the students. Also, frequency counts, mode and weighted mean were employed to establish the utilization level of gadgets, media apps/game apps, perceived cognitive and affective benefits. In addition, chi-square test  and  Cramers V or Phi  tests were used as effect sizes to measure strength  of relationship of profile variables to gadget and media games utilization level; perceived cognitive and affective benefits level. Stratified random sampling was employed in this study. Such sampling design helped the researcher determine a total of 169 teachers with different specializations such as English, Mathematics, Science and Technology and Livelihood Education (TLE) who served as respondents in this study. The Junior High School teachers perceived that multimedia games can give high cognitive and affective benefits. They perceived that media games were highly beneficial to the cognitive or brain development of the learners and there was a potential high affective benefits of students when exposed to media games.